2021
DOI: 10.3390/foods10122944
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Volatile Characterisation of Milk Inoculated with Thermo-Tolerant Lactobacillus bulgaricus through Adaptive Laboratory Evolution

Abstract: In this study, thermo-tolerant strain of Lactobacillus bulgaricus (L. bulgaricus) was developed using gradual increase in temperature to induce Adaptive Laboratory Evolution (ALE). Viable colony count of 1.87 ± 0.98 log cfu/mL was achieved at 52 °C, using MRS agar supplemented with 2% lactose. Changes in bacteria morphology were discovered, from rod (control) to filament (52 °C) to cocci after frozen storage (−80 °C). When milk was inoculated with thermo-tolerant L. bulgaricus, lactic acid production was absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…ALE was used as a tool to mainly improve or adapt LAB toward an increase in lactic acid production capacity, an increase in survival rate at acidic pH values, a better tolerance to different temperature conditions, a higher vitamin production, the maintenance of genetic stability of the strains under multiple stresses, and the investigation of how antibiotics can result in adaptations within the LAB genome. Among the different ways that ALE can be applied (Figure 2), it was observed that, of the 12 studies cited, seven utilized batch mode ALE (Zhang et al, 2012;Chen et al, 2015;Ming et al, 2016;Kwon et al, 2018;Prasad et al, 2020;Liang et al, 2021;Liu et al, 2021), one utilized the fed-batch mode method (Singhvi et al, 2018), and one utilized batch, fed-batch, and pulse fed-batch modes (Mladenović et al, 2019). The remaining works used distinct methods that are not described in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ALE was used as a tool to mainly improve or adapt LAB toward an increase in lactic acid production capacity, an increase in survival rate at acidic pH values, a better tolerance to different temperature conditions, a higher vitamin production, the maintenance of genetic stability of the strains under multiple stresses, and the investigation of how antibiotics can result in adaptations within the LAB genome. Among the different ways that ALE can be applied (Figure 2), it was observed that, of the 12 studies cited, seven utilized batch mode ALE (Zhang et al, 2012;Chen et al, 2015;Ming et al, 2016;Kwon et al, 2018;Prasad et al, 2020;Liang et al, 2021;Liu et al, 2021), one utilized the fed-batch mode method (Singhvi et al, 2018), and one utilized batch, fed-batch, and pulse fed-batch modes (Mladenović et al, 2019). The remaining works used distinct methods that are not described in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Cellular Division of these microorganisms can occur rapidly (20 min to 10 h/generation), for a few generations (100 to 500) (Sandberg et al, 2019). Thus, batch mode experiments are simple and the most widely used protocols for ALE and have been used in most of the articles cited in this review (Table 1) (Zhang et al, 2012;Chen et al, 2015;Ming et al, 2016;Kwon et al, 2018;Singhvi et al, 2018;Mladenović et al, 2019;Prasad et al, 2020;Liang et al, 2021;Liu et al, 2021).…”
Section: Adaptive Laboratory Evolution Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the bonds between protein and fat affected viscosity; changes in casein milk with the same hydrophilic properties as other protein types caused increased viscosity [55]. Fermentation of lactose produces lactic acid, which plays a role in milk protein to produce a unique gel-like texture and odor in yogurt [56].…”
Section: Yogurt Sensorial Analysismentioning
confidence: 99%